Ubiquitination as an Efficient Molecular Strategy Employed in Salmonella Infection - Narayanan, Lakshmi A.; Edelmann, Mariola J. (Frontiers in Immunology, 2014)
The protein modification with ubiquitin has various functions in the host innate immune system in response to the bacterial infection. To counteract the host immunity, Salmonella can specifically target ubiquitinating or deubiquitinating enzymes by its effector proteins. In this review we describe the multiple facets of ubiquitin function during infection with Salmonella enterica Typhimurium and hypothesize how these studies on the host-pathogen interactions can help to understand the general function of the ubiquitination pathway in the host cell.